Genesis, Development and Status of Environmental Sociology - Trempała, Wojciech (Studia Ecologiae et Bioethicae, 2016)
The process of the international identification of global ecological problems, initiated in the 1970s, enlivened the discussion on the character of relations between man and natural environment in the context of many humanistic and social disciplines. It also applies to sociology, whose representatives are frequently unjustly associated with attachment to their own scientific autonomy. The latter should consist in explaning the phenomenon of social life only with the use of social facts treated in separation from the impact of nature. The purpose of this article is an attempt of the deconstruction of genesis, development, and status of environmental sociology in the United States and Poland. In the former, this subdiscipline originated there and reported the greatest growth, whereas in the latter, its accomplishments remain dissipated, despite the fact that in some research areas – for instance in the scope of empirical descriptions of awareness and ecological attitudes of the public – it constitutes a coherent, valuable entirety. At the same time, the task of the author is popularization of history, traditions, and assumptions of environmental sociology, which contribution to the fight with the environmental crisis, although underestimated, is as substantial as the one developed in the scope of eco-philosophy led by environmental ethics, a leading field among humanistic and social studies.